Sustainable Livelihood and Effective Disaster Response: A Case Study of Phailin Cyclone of Odisha, India - Panda, Damodar; Anand, Rashmi Rani; Devi, Maya (Prevention and Treatment of Natural Disasters, 2025)
The Odisha coast is one of the most cyclone‑prone areas of India. In recent years, the state experienced two catastrophic tropical cyclones: the 1999 Super Cyclone and Phailin in 2013. Due to the impact of cyclones, the infrastructure and occupation of the people are severely affected. In coastal Odisha, people primarily rely on agriculture, livestock, pisciculture, and horticulture for their livelihoods. Storm winds, heavy rainfall, and storm surges from sea waves inundate cultivable land, damage horticultural plants, and kill domestic animals and poultry birds. The state government provides financial assistance for the recovery of the loss, which is inadequate. Therefore, people find an alternate source of income to overcome the loss. This research article aims to explore the relationship between disaster management and livelihood security in the context of Very Severe Cyclone Phailin. The study demonstrates that community‑level cooperation and government support at the state and national levels in disaster risk reduction have led to the protection of human life and a decrease in people’s suffering. To make disaster management effective, the government’s initiatives in community involvement in preparedness, response, and recovery can reduce disaster risk and protect the livelihoods of vulnerable people. This article examines various measures implemented by the government and proposes necessary improvements to mitigate disaster risk in livelihood support following tropical cyclones in the state.